Strategic enterprise management and application to the telecommunications industry - Yakut, Lale (My University, 2003)
Strateji-odaklı organizasyon, hedef ve amaçlarını kıt ve belirsiz zaman ve kaynaklarla eyleme dönüştürebilen organizasyondur. Başarıya giden yolda, bir şirketin karlılık hedefleri daima kısa vadeli finansal hedeflerle ile belirlenememektedir, zira maddi olmayan duran varlıkların rekabetçi avantaj yaratmada ana kaynak olmaya doğru önemli yol kat ettiği günümüz ekonomilerinde, finansal olmayan, bilgi bazlı ve katma değer yaratan stratejiler daha fazla önem arz etmektedir. Bu çerçevede, organizasyonların, stratejilerini operasyon diline ve eylem planlarına dönüştürmek için etkin araçlar kullanmaları, aynı zamanda, başarılarını maddi olmayan varlıklarını da göz önüne alarak ölçmeleri gerelmektedir. Balanced Scorecard (Dengelenmiş Performans Yönetimi) organizasyonların stratejik amaçlarını ilgili performans ölçütlerine çeviren ve geleneksel tarihsel finansal verilerle niteliksel verileri bütünleştiren entegre bir stratejik işletme yönetimi yapısıdır. Bu çalışmada, öncelikle, stratejinin, ve strateji-odaklı işletmenin temellerini ayrıca strateji oluşturmadaki modern yaklaşımları inceleyeceğiz. Bu araçlardan Balanced Scorecard üzerinde ayrıntılı olacak duracağız. Daha sonra binden fazla çalışanı ile Türkiye pazarında sektöründe üçüncü sırada bir telekomünikasyon şirketinde detaylı bir uygulama çalışması yapacağız. Fiktif değerlerle yapılan hedef ve fiili karşılaştırmalı Balanced Scorecard'ımızı uygulayarak değerlendirmeler bölümü ile tezimizi tamamlayacağız. Tezin uygulama aşamasında Dialog Software, SAP SEM/ CPM (Strategic Enterprise Management / Corporate Performance Monitor) ve MsExcel yazılımlarını kulanacağız. A strategy-focused organization is the one that translates its goals and objectives into action under uncertainty and insufficiency of time and resources most effectively. On the way to success, however, profitability of an organization cannot be measured based on short-term financial goals since in today's economies, where intangible assets have become the major sources of competitive advantage, tools that describe knowledge-based assets and the value creating strategies that these assets have been creating greater influence and importance. In this context, organizations have to deploy efficient tools in order to translate their strategies into operational terms and consequent actions, correspondingly measure their success by taking into consideration their non-financial data, that is intangible assets. For this purpose, Balanced Scorecard is an integrated strategic performance management framework that helps organizations translate strategic objectives into relevant performance measures integrating traditional historical-based financial key figures, with qualitative factors. In this study, we will try to analyze the fundamentals of strategy, and strategy-focused organization, taking a look at contemporary approaches in building strategy. The section will be followed with Balanced Scorecard methodology in detail. Afterwards, we will present an implementation proposal for Balanced Scorecard in a telecommunications company operating in Turkish market with around one thousand employees and enjoying the third place in the market share. The study including the plan/ actual comparisons with fictitious values will be concluded with results and evaluations chapter. We will use Dialog Software, SAP SEM/ CPM (SAP Strategic Enterprise Management / Corporate Performance Monitor) and Microsoft Excel softwares in the application chapter.
Keywords: Endüstriyel Yönetim; Genel yönetim